Lifestyle and risk of diabetes mellitus - Tercero Chicaiza , Mishel Pamela (2022)
Diabetes Mellitus is one of the chronic diseases that cause great impact on the quality of life of people, by decreasing the physical capacity due to the multi-organ complications that it generates, so it is important to maintain a good quality of life, that is why the objective of this essay was; "To determine the lifestyles and risks of diabetes mellitus in the Papahurco community in the Salcedo canton of the province of Cotopaxi", for which a quantitative research of descriptive type was developed, selecting 144 people by probabilistic sampling for finite populations. The information was collected by applying the Findrisk scale, after the descriptive statistical analysis it was determined that 26.4% of the people who made up the sample were between 35 and 44 years of age; 20.1% had a BMI over 30kh/m2 ; 90.3% of the women and 77% of the men had CA above the normal value; 57.6% performed 30 min/day of physical activity; 59% ingested fruits and vegetables daily; 57.6% had direct family or relatives with DM; 50% had high glucose values. Conclusion: in general, the population of the Papahurco community presented a slightly elevated risk of developing type 2 diabetes mellitus.